Appreciation of different styles of humor: An fMRI study. Issue 1 (December 2018) - Chan, Yu-Chen; Hsu, Wei-Chin; Liao, Yi-Jun; Chen, Hsueh-Chih; Tu, Cheng-Hao; Wu, Ching-Lin
Abstract Humor styles are important in facilitating social relationships. Following humor styles theory, this functional magnetic resonance imaging (fMRI) study is the first to use "one-liner" humor to investigate the neural correlates involved in appreciating humor styles that differ in terms of target (self or other) and motivation (benign or detrimental). Interestingly, we observed greater activation in response to humor that facilitates relationships with others (self-defeating and affiliative humor) than to humor that enhances the self (self-enhancing and aggressive humor). Self-defeating humor may play an important role in Chinese culture in facilitating social relationships at one's own expense. Psychophysiological interaction (PPI) analysis revealed temporal pole (TP)-frontal functional connectivity underlying the appreciation of self-directed humor, and temporo-parietal junction (TPJ)-frontal connectivity underlying the appreciation of other-directed humor. Amygdala-frontal coupling was observed during the appreciation of detrimental humor, while nucleus accumbens (NAc)-temporal coupling and midbrain-frontal coupling appear to play a role in the affective experience of amusement in response to benign humor. This study contributes to our understanding of the neural correlates of appreciating different humor styles, including humor that facilitates social relationships.